Evolution of Risks Facing Commercial Banks in Kenya and Associated Strategic Responses - Kimani, John; Kibera, Margaret (International Journal of Modern Risk Management, 2023)
Purpose: The main objective of this study was to explore the evolution of risks facing commercial banks in Kenya and their strategic responses Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The study found that the commercial banking sector in Kenya is operating within a highly dynamic and ever-evolving risk landscape. The risks faced by these banks are multifaceted and include economic, operational risk, regulatory, technological, systematic, sovereign risk and market-related challenges. It also added that the strategic responses adopted by commercial banks in Kenya are diverse and multifaceted. The conclusions drawn emphasize the need for continual vigilance and adaptation in risk management, the pivotal role of technology and digital transformation, and the significance of regulatory compliance. By taking these conclusions into account, commercial banks in Kenya can better position themselves to thrive in the dynamic and competitive financial landscape of the country. Unique Contribution to Theory, Practice and Policy: The Modern Portfolio theory, liquidity preference and the Liquidity Coverage Ratio (LCR), Agency theory, the term structure of interest rates and duration and Credit Scoring Model and the Resource Based View model may be used to anchor future studies on the evolution of risks facing commercial banks in Kenya and their strategic responses. This study makes significant contributions to theory by developing a risk evolution framework and strategic risk response models. It has practical implications by offering enhanced risk management strategies and guidance for financial decision-making for practitioners. Additionally, the research provides valuable insights for banking regulators policymakers, and investors in Kenya, supporting risk-based supervision and financial stability initiatives.